Cilengitide downmodulates invasiveness and vasculogenic mimicry of neuropilin 1 expressing melanoma cells through the inhibition of αvβ5 integrin. Issue 6 (28th November 2014) - Ruffini, Federica; Graziani, Grazia; Levati, Lauretta; Tentori, Lucio; D'Atri, Stefania; Lacal, Pedro M.
<x xml:space="preserve">Abstract</x> During melanoma progression, tumour cells show increased adhesiveness to the vascular wall, invade the extracellular matrix (ECM) and frequently form functional channels similar to vascular vessels (vasculogenic mimicry). These properties are mainly mediated by the interaction of integrins with ECM components. Since we had previously identified neuropilin 1 (NRP‐1), a coreceptor of vascular endothelial growth factor A (VEGF‐A), as an important determinant of melanoma aggressiveness, aims of this study were to identify the specific integrins involved in the highly invasive phenotype of NRP‐1 expressing cells and to investigate their role as targets to counteract melanoma progression. Melanoma aggressiveness was evaluated in vitro as cell ability to migrate through an ECM layer and to form tubule‐like structures using transfected cells. Integrins relevant to these processes were identified using specific blocking antibodies. The αvβ5 integrin was found to be responsible for about 80% of the capability of NRP‐1 expressing cells to adhere on vitronectin. In these cells αvβ5 expression level was twice higher than in low‐invasive control cells and contributed to the ability of melanoma cells to form tubule‐like structures on matrigel. Cilengitide, a potent inhibitor of αν integrins activation, reduced ECM invasion, vasculogenic mimicry and secretion of VEGF‐A and metalloproteinase 9 by melanoma cells. In conclusion, we demonstrated that ανβ5 integrin is involved in the highly aggressive phenotype of melanoma cells expressing NRP‐1. Moreover, we identified a novel mechanism that contributes to the antimelanoma activity of the αv integrin inhibitor cilengitide based on the inhibition of vasculogenic mimicry.